Intracholecystic Papillary Neoplasm- A Case Report: Intracholecystic Papillary Neoplasm - Choudhury, Tamanna; Razzaque, Sabrina; Begum, Mahbuba; Ahmad, Rahnuma (Journal of the Medical College for Women & Hospital, 2025)
Intracholecystic Papillary Neoplasm (ICPN) is a rare entity and is a premalignant lesion of the gallbladder. It is usually an incidental finding on imaging and can only be diagnosed on histomorphological evaluation. Here we report a case of ICPN in a 40 year old woman who had a short history of abdominal pain. Ultrasound examination of the abdomen revealed multiple polyps in the gallbladder. Laparoscopic cholecystectomy was done and diagnosed as ICPN on histopathological examination. J Med Coll Women Hosp.2025; 21 (2):150-156